Tội phạm quốc tế = (Công ty Cổ phần phim Thiên Ngân, 2009)
Interpol agent Louis Salinger (Clive Owen) is determined to expose an arms dealing ring responsible for facilitating acts of terrorism around the globe. But as his investigation leads Salinger and his partner, Manhattan Assistant District Attorney Eleanor Whitman (Naomi watts), deeper into the secret world of greed, corruption and murder, they become targets of a deadly conspiracy so vast, they soon find the only people left to trust... are each other.